PERBEDAAN TINGKAT FORGIVENESS PADA SISWA KORBAN BULLYING DAN BUKAN KORBAN BULLYING DI SMP X KOTA BEKASI - Lani Pranesti; Lenny Utama Afriyenti; Rizma Afian Azhiim (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
The phenomenon of bullying in junior high schools (SMP) remains a serious concern due to the emotional distress and deep psychological wounds it inflicts on victims. This study aims to examine differences in forgiveness levels between student victims and non-victims of bullying at SMP X, Bekasi City. The method used was a quantitative approach with a comparative design, involving 98 students from grades 7, 8, and 9 selected through convenience sampling via a screening process, using the Transgression-Related Interpersonal Motivations Scale-18 (TRIM-18), which demonstrated adequate reliability (α = 0.785). The results showed p = 0.432 (p > 0.05), indicating no statistically significant difference in forgiveness levels between bullying victims and non-victims. Most students in both groups fell into the moderate forgiveness category, with comparable mean scores across groups. Future research is suggested to use a more structured bullying-status classification and examine other psychological factors influencing forgiveness levels.